Nonequilibrium plasmons and transport properties of a double-junction quantum wire - Kim, Jaeuk U.; Choi, Mahn-Soo; Krive, Ilya V.; Kinaret, Jari M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
We study theoretically the current-voltage characteristics, shot noise, and full counting statistics of a quantum wire double barrier structure. We model each wire segment by a spinless Luttinger liquid. Within the sequential tunneling approach, we describe the system’s dynamics using a master equation. We show that at finite bias the nonequilibrium distribution of plasmons in the central wire segment leads to increased average current, enhanced shot noise, and full counting statistics corresponding to a super-Poissonian process. These effects are particularly pronouncedin the strong interaction regime, while in the noninteracting case we recover results obtained earlier using detailed balance arguments.